Kolaborasi Guru dengan Orang Tua dalam Merancang dan Melaksanakan Pembelajaran Metamorfosis - Maftuhah, Siti; Wuryastuti, Sri; Suratno, Tatang (Universitas Pendidikan Indonesia Kampus Serang, 2022)
Learning is a series of activities carried out by teachers to transmit knowledge to students. The success of children's education depends on various environmental factors in children's education. The first education for children is family education because, in family education, children are the first to receive parenting education, guidance, and training. When parents carry out the task of educating, they cannot fully meet the educational needs of their children. Therefore, these tasks are given by school teachers because teachers have knowledge and knowledge, especially in education. However, the Covid-19 outbreak has affected educators, parents, and students who need to adapt to the changes. The face-to-face learning system was originally carried out with a bold learning system (on the network). Therefore, it is necessary to have learning that is following the environment, especially learning at home, one of which is by applying metamorphosis learning in science subjects. This study aims to find out the form of collaboration between teachers and parents in designing and implementing metamorphosis learning and the process of knowing students in carrying out metamorphosis learning at home. This study uses a case study method because there are several limitations in the study. The results of this study indicate that applying metamorphosis learning can teach students to learn independently in their observations so that the burden of parents in helping their children learn is not too heavy. Therefore, the importance of collaboration between teachers and parents to carry out bold learning well.